A Helpful Guide for Parents and Guardians of People on the Autism Spectrum Disorder - Knowing Your Main Rights - Masoura, Photini; Skitsou, Alexandra; Dre, Marianna; Charalambous, Georgios (HAPSc Policy Briefs Series, 2022)
Autism is a serious developmental disorder that affects people throughout their lives, affecting their perception, thinking and behavior. It has been observed that there is a lack of information regarding the rights of parents and guardians of children on the autism spectrum, especially those of vulnerable social groups. A short guide was written in order to inform the parents and guardians about their rights. Furthermore, a bibliographic review of the international, European and Greek legislation framework was carried out and we came to the conclusion that there is an extensive legislation framework for the protection of the rights of individuals on the autism spectrum and their parents.